The Effect of Premature Neonates Massage by Mothers on Maternal Anxiety and Self-Esteem: A Randomized Clinical Trial - Fatemeh Abbasi; Leila Abadian; Hadi Ranjbar; Aida Safaiee Fakhr; Batool Pouraboli; Aida Ravarian (Mashhad University of Medical Sciences, 2023)
Background: Mothers experience challenges when a premature infant is born and admitted to the neonatal intensive care unit (NICU).Aim: The present study was conducted with aim to investigate the effect of infant massage by the mother on maternal anxiety and self-esteem.Method: This randomized clinical trial study was performed on mothers of 63 premature infants admitted to the neonatal intensive care unit. Mothers were randomly assigned into the intervention and control groups. Mothers in both groups completed Rosenberg's Self-esteem and Beck Anxiety questionnaires. The mothers in the intervention group were trained to massage their infants. They applied a 15-minute massage 3 times a day for two weeks. The mother in the control group received routine education of hospital including pamphletes and self relaxation techniqes. After two weeks, the mothers in both groups again completed Rosenberg Self-esteem and Beck Anxiety questionnaires. Data were analyzed by SPSS (version 16) and Mann-Whitney U and Wilcoxon test. p<0.05 was considered statisically significant.Results: The mean score of anxiety reduced more significantly in the intervention group compared to the control group (39.12 vs. 11.52) (p<0.05). The mean score of self-esteem showed a 16.94-point increase in the intervention group compared to 1.58 points increase in the control group (p<0.05).Implications for Practice: Massage of premature infants by their mothers is a useful and cost-effective way to reduce maternal anxiety and increase maternal self-esteem in the NICUs. Therefore, educating this technique is recommended in the NICUs.